2020
DOI: 10.2478/raon-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of set-up errors in the radiotherapy of patients with head and neck cancer: standard vs. individual head support

Abstract: AbstractBackgroundThe aim of the study was to (a) compare the accuracy of two different immobilization strategies for patients with head and neck tumors, and (b) compare the set-up errors on treatment units with different portal imaging systems.Patients and methodsVariati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Androjna et al. 11 results also reflect those found in our study, the authors found a statistically significant decrease in set up errors on a CHR compared to SHR in a large sample of 120 patients. The greatest reduction was seen in the vertical direction of 0.7 mm.…”
Section: Discussionsupporting
confidence: 92%
“…Androjna et al. 11 results also reflect those found in our study, the authors found a statistically significant decrease in set up errors on a CHR compared to SHR in a large sample of 120 patients. The greatest reduction was seen in the vertical direction of 0.7 mm.…”
Section: Discussionsupporting
confidence: 92%
“…When using SGRT‐only patient setup and motion monitoring, the patient immobilization device is important, and here, the SGRT‐only setup accuracy is derived from the CDR system with customized head mold and open‐face mask. It has been reported that patient setup accuracy is higher using individual customized head support compared with standard headrest 31 . In addition, the customized head immobilization system also provides much higher patient motion restriction, reducing possible intrafractional patient motion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patient setup accuracy is higher using individual customized head support compared with standard headrest. 31 In addition, the customized head immobilization system also provides much higher patient motion restriction, reducing possible intrafractional patient motion.…”
Section: B | Clinical Benefits For Sgrt-only Setup and Option For Motion Monitoringmentioning
confidence: 99%
“…Although fixed headrest with a head mask is the conventional postural fixation for intracranial tumor radiotherapy, it can shrink and deform over time, thus affecting the positional accuracy of patient treatment. However, personalized custom headrests can avoid this problem and improve radiotherapy accuracy (6). Ghazal Shafai-Erfani et al (7) found systematic errors of 1.1, 2.0, and 2.3 mm in the left-right, head-foot, and anterior-posterior directions, respectively, for the headrest plus mask fixation technique.…”
Section: Introductionmentioning
confidence: 99%